2009
DOI: 10.1089/apc.2008.0256
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of HIV-Related Stigma Among Young Men Who Have Sex with Men

Abstract: Young men who have sex with men (MSM) represent an increasing number of new HIV infections in many communities. Many individuals still hold beliefs that may lead to discrimination against HIV-positive individuals. HIV stigma is associated with negative health and psychosocial outcomes and may lead to greater challenges for this marginalized population. This study describes stigma experienced by HIV-positive young MSM, explores its relationship to psychosocial measures, and tests the hypothesis that stigma scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
123
2
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(137 citation statements)
references
References 25 publications
10
123
2
2
Order By: Relevance
“…This incidental finding stands in contrast to prior studies, which suggest that perceptions of HIV stigma may decrease over time following an initial HIV diagnosis. 11,36 Similarly, biologic markers of disease progression (i.e., CD4 count, viral load) did not relate to stigma variables in the current study, despite past research suggesting that HIV stigma may become exacerbated by increased disease progression and symptomatology. The current study was not designed to examine these linkages, and null findings may reflect power limitations of the small sample size.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…This incidental finding stands in contrast to prior studies, which suggest that perceptions of HIV stigma may decrease over time following an initial HIV diagnosis. 11,36 Similarly, biologic markers of disease progression (i.e., CD4 count, viral load) did not relate to stigma variables in the current study, despite past research suggesting that HIV stigma may become exacerbated by increased disease progression and symptomatology. The current study was not designed to examine these linkages, and null findings may reflect power limitations of the small sample size.…”
Section: Discussioncontrasting
confidence: 79%
“…9,10 The current study focuses on stigma, which is one factor thought to be particularly salient to African American MSM infected with HIV. [9][10][11] Emerging research suggests that young MSM infected with HIV may experience multiple forms of stigma related to both their sexuality and seropositive status. 12,13 HIV stigma may be particularly salient for young MSM who are African American, since research suggests that HIV-positive African Americans experience higher levels of HIV stigma than both Latinos and whites.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One of the key informant interviewees also identified the negative attitudes of providers as a factor in deterring clients from returning to HIV clinics. This finding is consistent with another study conducted with MSM and transgender women in Thailand that reported high rates of perceived hostility from healthcare providers and being given less attention than other patients [13]. These results suggest that future interventions should include efforts to reduce discrimination in the healthcare system.…”
Section: Discussionsupporting
confidence: 89%
“…However, because many MSM may not report their sexual orientation to healthcare providers or HIV testing centers because of fear of stigma [8], prevalence of HIV/AIDS among MSM maybe under-reported [4]. HIV-positive MSM in Thailand experience stigma associated with being MSM and significant discrimination because of their HIV status [8], putting them at risk for poorer healthcare utilization and negative health outcomes [13].…”
Section: Men Who Have Sex With Men Living With Hiv In Thailandmentioning
confidence: 99%